1998
DOI: 10.1080/001075198181775
|View full text |Cite
|
Sign up to set email alerts
|

Ionic channels in biological membranes- electrostatic analysis of a natural nanotube

Abstract: Ionic channels are proteins with holes down their middle that control access to biological cells and thus govern an enormous range of biological functions important in health and disease. A substantial fraction of the drugs used in clinical medicine act directly or indirectly on channels. Channels have a simple well defined structure, and the fundamental mechanism of ionic motion is known to be electrodiffusion. The current through individual channel molecules can easily be

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 125 publications
0
64
0
Order By: Relevance
“…The PNP model suffers from at least three difficulties, even in three dimensions (Eisenberg, 1998a;Eisenberg, 1998b;Eisenberg, 1996b;Horn, 1998): it lacks chemistry and single filing, it lacks spatial resolution, and it does not deal with protein conformation changes thought to underlie gating.…”
Section: Brief History Of Diffusion Theory Of Chemical Reactions Thementioning
confidence: 99%
See 1 more Smart Citation
“…The PNP model suffers from at least three difficulties, even in three dimensions (Eisenberg, 1998a;Eisenberg, 1998b;Eisenberg, 1996b;Horn, 1998): it lacks chemistry and single filing, it lacks spatial resolution, and it does not deal with protein conformation changes thought to underlie gating.…”
Section: Brief History Of Diffusion Theory Of Chemical Reactions Thementioning
confidence: 99%
“…(Otherwise, the simulations could not be used to design real transistors, which require bias potentials to function usefully.) Physicists familiar with these methods might find them revealing if applied to systems of ions and channels (Eisenberg, 1998a).…”
Section: Brief History Of Diffusion Theory Of Chemical Reactions Thementioning
confidence: 99%
“…Within the framework our data, the observed increase of the overall conductance of the alamethicin channel when cholesterol is part of the biomembrane composition, can be viewed as a consequence of a dipole moment decrease caused by cholesterol. In order to qualitatively check the influence of dipole potential alterations on the overall conductance of an over-simplified conducting pore embedded into a model biomembrane, we have conducted a simulation based on the Poisson-Nernst-Planck theory [23]. We found that in the case of the alamethicin pore, which shows modest selectivity for monovalent cations (P + /P − = 4) [31], a simulated decrease of the dipole potential leads to an increase in the electric conductivity, which is in agreement with the experimental data.…”
Section: Discussionmentioning
confidence: 99%
“…When cholesterol-containing asymmetric bilayer membranes were to be used, one of the lipid leaflets contained growing amounts (10 %, 20 % and 50 % w/w -with respect to the total mass achieved) of cholesterol (Sigma-Aldrich). In order to simulate the effect of bilayer's dipole potential modification induced by cholesterol on the electrical conductance through alamethicin oligomers, we resorted to the use of the Poisson-Nernst-Planck theory [23]. The perturbing effect of cholesterol on the magnitude of the biomembrane dipole moment was modelled as a relative decrease of the electrical dipole field within the polar region of the biomembrane.…”
Section: Methodsmentioning
confidence: 99%
“…The PNP equations were suggested as the basic continuum model for open ion channels by Eisenberg and coworkers [7,19,20] and were numerically solved and compared with real experimental I-V curves in many papers; see [21,22, and references therein]. PNP has long been used outside the channel world as the simplest combination of constitutive and conservation laws that are useful in describing electrodiffusion.…”
Section: Introductionmentioning
confidence: 99%